2016
DOI: 10.1038/nature16500
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2 maintains haematopoietic stem cells with extensive lymphoid potential

Abstract: Hematopoietic stem cells (HSCs), which sustain production of all blood cell lineages,1 rely on glycolysis for ATP production,2,3 yet little attention has been paid to the role of mitochondria. We show here that the short isoform of a critical regulator of HSCs, Prdm16,4,5 induces mitofusin 2 (Mfn2), a protein involved in mitochondrial fusion and in tethering of mitochondria to the endoplasmic reticulum (ER). Overexpression and deletion studies, including single cell transplantation assays, revealed that Mfn2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
164
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 35 publications
(46 reference statements)
11
164
1
Order By: Relevance
“…Consistently, miR-106b targeted the 30 untranslated regions (30 UTRs) of Mfn2, and Mfn2 proteins were abundant at the post-transcriptional level so that miR-214 could regulate Mfn2 gene at the posttranscriptional level [15, 32]. Previous studies have shown that miR-214 was overexpressed in MSCs of mice, but the expression of Mfn2 was lower in hematopoietic stem cells [9, 33]. In addition, adult bone marrow (BM)-derived stem cells were generated from HSCs and MSCs represented an important cell source for damaged tissue repair, indicating that the expression of Mfn2 decreases in rADMSCs [34].…”
Section: Discussionmentioning
confidence: 98%
“…Consistently, miR-106b targeted the 30 untranslated regions (30 UTRs) of Mfn2, and Mfn2 proteins were abundant at the post-transcriptional level so that miR-214 could regulate Mfn2 gene at the posttranscriptional level [15, 32]. Previous studies have shown that miR-214 was overexpressed in MSCs of mice, but the expression of Mfn2 was lower in hematopoietic stem cells [9, 33]. In addition, adult bone marrow (BM)-derived stem cells were generated from HSCs and MSCs represented an important cell source for damaged tissue repair, indicating that the expression of Mfn2 decreases in rADMSCs [34].…”
Section: Discussionmentioning
confidence: 98%
“…Mitofusin 2 (Mfn2) deficiency mainly affects lymphoid-but not myeloid-dominant HSCs in the HSC population. Mfn2 activity modulates calcium signaling and negatively regulates nuclear translocation of nuclear factor of activated T cells (Nfat) to sustain lymphoid potential [26].…”
Section: Role Of the Tca Cycle And Oxphos In Hsc Differentiationmentioning
confidence: 99%
“…Mitochondrial dynamics also affect cellular processes involved in stem cell pluripotency. mitochondria to the endoplasmic reticulum, thereby inhibiting nuclear factor of activated T cells (Nfat) transcriptional activity [89 ]. This mechanism is required for maintenance of hematopoietic stem cells with extensive lymphoid potential.…”
Section: Mitochondrial Fusion and Fissionmentioning
confidence: 99%